Ultrasonographic Predication of Gestational Age and Expected Whelping Date in Canine (Canis familiaris) - Yadav, Lakshmi; Sarswat, Chander Shekar; Purohit, Shivani; Gurjar, Kuldeep singh; Yadav, Sumit Prakash; Kumar, Hitesh (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during August, 2023 to March, 2024 at Veterinary Clinical Complex in department of Veterinary Gynaecology and Obstetrics, Post Graduate Institute of Veterinary Education and Research (PGIVER) Jaipur to study the gestational age during pregnancy in different breeds (Canis familiaris) by using various ultrasonographic parameters such as Gestational Sac Diameter (GSD), Head Diameter (HD), Crown Rump Length (CRL) and Body Diameter (BD) and to also study the expected and actual whelping date in different breeds (Canis familiaris). Using ultrasound, 30 bitches’ pregnancy diagnoses were determined. The bitches were examined during different phases. 11 pregnant bitches were examined during first phase 20 to 30 days’ post mating, 6 pregnant bitches were examined during second phase 30 to 45 days’ post mating and 13 pregnant bitches were examined in third phase 45 to 60 days’ post mating. During first phase Gestational sac diameter was measured, during second phase Crown rump length was measured and during third phase Head diameter and Body diameter were measured. During first phase the mean (±SE) gestational sac diameter was 1.23±0.12 cm. The calculated gestational age by using formula I was found to be 27.4±0.74 days. The difference between expected and actual whelping date during this phase mean (±SE) was -2.36±0.20 days. During the second phase the mean (±SE) CRL measurement was 2.99±0.28 cm. The calculated gestational age by using formula II mean (±SE) found to be 35.96±0.85 days. The difference between expected and actual whelping date during this phase mean (±SE) was -1.5±0.62 days. During the third phase the mean (±SE) BPD was 2.04±0.08 cm and BD was 3.37±0.14 cm. The calculated gestational age by formula III mean (±SE) was 50.57±1.33 days, by formula IV mean (±SE) was 52.59±1.01 days and by formula V mean (±SE) was 52.34±0.88 days. The difference between expected and actual whelping date mean (±SE) was -1.85±0.52 days.